Assessment of workers’ knowledge and views of occupational health hazards of gold mining in Obuasi Municipality, Ghana - Atakora, Michael; Stenberg, Berndt (International Journal of Occupational Safety and Health, 2020)
Background: Small-scale mining in Ghana has been a major community and national concern due to its contribution to the destruction of farmlands and bodies of water, and to the loss of human life. Small-scale mining exposes workers to varying degrees of health hazards and problems. Objectives: The study aimed to assess the knowledge and views of workers about the occupational health hazards and problems related to small-scale gold mining in Obuasi Municipality, Ghana, to help improve workers’ safety at the mining sites. Methods: A cross-sectional study was done between May and December 2011. Simple random sampling was used to select 150 small-scale miners take part in this study. The workers were asked about their knowledge and views of occupational health hazards and problems related to gold mining. Data were entered with EpiData Entry 3.1 and analyzed using Stata 11. Results: Most workers (63.3%) had low knowledge of occupational health and safety regulations. Multivariable logistic regression analysis showed that knowledge about regulations was associated with level of education (OR = 8.5; 95% CI: 7–10.5). The common effects of mining that workers expressed awareness of were land pollution (30%), water pollution (28%), air pollution (18.7%), and noise pollution (16%). The factors influencing exposure to health hazards related to mining were low educational levels (14%), little work experience (30.7%), incorrect handling of equipment or chemicals (26%), poor law enforcement (12.7%), and negligence (16.7%). In general, occupational lung disease (16%), occupational hearing loss (14%), heat illnesses (12%), eye infections (16%), malaria (24%), and skin infections (18%) were the most common health problems study participants mentioned. Conclusion: High levels of occupational health hazards and problems related to gold mining exist among workers in private mines. Safety program should be offered as part of associated public health programs to limit the most significant risks. We further recommend education and training on regulations and the use of personal protective equipment.